DEVELOPMENT OF HUMAN BALANCE CAPABILITY TESTING PROTOTYPE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The detection of human balance functional disorders may provide some kind of awareness or even warning about potential problems for human health both in organs responsible for ensuring the balance function and in organs related to fulfilment of other important life functions. Modern world offers some sophisticated solutions which enable not only determination of the human balance functional capacity but also offer some kind of training environment to provide corresponding rehabilitation. Unfortunately, such systems are very expensive. And this make limitations of their accessibility and practical usability for a wide range of the target group / population. Software solutions, including mobile applications, on the other hand, are incomparably cheaper. However, they do not allow to make precise balance capability measurements, limiting to simplified balance retention simulators.During implementation of the Latvian National State Research Program VPP INOSOCTEREHI from 2015 to 2017 three human balance capability testing prototypes were developed using a variety of electronic and mechatronic solutions. The last one was successfully approbated during two pilots in Latvian schools in 2016 and demonstrated at the International Invention and Innovation Exhibition MINOX-2016. This paper analyses benefits and disadvantages of approaches used in creating of these prototypes. Besides, authors make initial comparison of developed third prototype version against the BioSway system offered in the market. The paper gives also insight into particular system interface development and new effective graphic portrayal of the balance testing output data, as well as sets the goals for further possible commercialization of the developed balance testing prototype.